PERBANDINGAN ANTARA PEMBERIAN ASAM FOLAT, EKSTRAK GINKGO BILOBA, DAN METHYL COBALAMIN TERHADAP INDEKS APOPTOSIS DAN EKSPRESI CASPASE 3 PADA INTOKSIKASI METANOL SEL GANGLION RETINA - Prayitnaningsih, Seskoati; Sumarno, Sumarno (Fakultas Kedokteran Universitas Brawijaya, 2005)
ABSTRACT Permanent visual damage caused by methanol intoxication has been associated with prolonged exposures to blood formate concentrations. Formate accumulation disrupt mitochondrial energy production, which subsequently lead to caspase 9, 3 activation and finally causes apoptosis. Folic acid (FA) has been used as adjunctive therapy to enhance the rate of formate metabolism. Extract Ginkgo biloba (EGb) the most popular herbal therapy possess is antioxidant and antiapoptotic capacity. On the other hand, Methyl cobalamin, a kind of endogenous co enzyme B 12 can promote nucleic acid and protein synthesis. To compare the effect of FA, (EGb), and Methyl Cobalamin (MC) to Apoptotic Index (AI) and Caspase 3 expression of retinal ganglion cell induced by methanol intoxication (MI). Experimental study was conducted in Pharmacology and Biomedic laboratory of Brawijaya University for two weeks. Fifteen rats were included, and divided into five groups: (a) control, (b) Methanol Intoxication only, (c) Folic Acid 1 mg day per os, (d) Extract Ginkgo biloba 50 mg/kb per os, and (e) Methyl Cobalamin 500 microgram/kg intraperitoneally for three days. MI were done by giving methanol 4 g/kg in the first day, and 2 g/kg for two days after. Apoptotic Index and Caspase 3 expression were assessed